THE STRUGGLE TO FIND HIS PARENTS IN "AUGUST RUSH" KIRSTEN'S SHERIDAN'S MOVIE: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - PRAYOGI, PUDIO IQBAL (2011)
The study is to reveal how the struggle to find his parents of the major character influences his personality. The objective of this study is to analyze the movie based on the structural analysis and the individual psychological analysis. This study is a qualitative study. The object of the study is Kirsten Sheridan's "August Rush" movie. The data sources are divided into two, namely primary data source and secondary data source. The primary data is the movie itself, "August Rush" by Kirsten Sheridan, and the secondary data source are the other literatures and virtual references which are relevant to the film. The method of data collection is watching the movie repeatedly, understanding the movie, focusing Evan Taylor's struggle to find the joy in his life, listing the event and uses library research by collecting and selecting the appropriate data from many sources. The technique of data analysis is descriptive analysis. This study attempts to dissect the narrative elements of film into narrative elements and technical elements. The narrative consists of character and characterization, plot, setting, point of view, theme and casting. Meanwhile, technical elements involve Mise en Scene and sounds. This study will analyze the main character of the story, namely, Evan Taylor or August Rush. It is viewed from psychological aspect. It refers to the application of the individual psychological theory proposed by Alfred Adler. The theory consists of six basic principles of individual psychology, that are fiction finalism, inferiority feeling, striving for superiority, style of life, social interest, and creative power. In August Rush, Kirsten Sheridan, creates the major character of the movie namely, Evan Taylor. From the beginning to the end of the movie, he represents Evan as human being who tries to make his life better by struggle. He also shows Evan's effort finding his parents by learn music. Sheridan also adds other characters to support the major character to be more vivid. He puts them together with their own background, in a setting, which permits them to support each other. Sheridan creates those characters as the means of expressing what he wants to say and think although the content of the movie is almost dominated by the major character story in facing his life, but other character have a lot of roles. In this movie Sheridan takes the setting of place, generally in the America, particularly in New York. He also takes the setting of time in 2007. In August Rush, Kirsten Sheridan uses combining point of view. vii Because Evan stating the name or personal person and also involved in a story. The theme of this story is "the dreams will be achieve with strong faith". Evan Taylor has some efforts to get his desire. He uses his faith that if he could learn to play music he will have a chance to be found by his parents. His effort is done to gain his goal, his desire is to find and live with his parents. August Rush is the reflection of the human trying to get his desire. The author wants to describe how human beings have many ways making his dream come true. He also wants to show that human are full of imagination and desire. It is shown when August has a desire and works hard in fulfilling it. In this movie, Kirsten Sheridan describes August as a person who always tries to fulfill his wish by struggling and striving to make all dreams become true, the psychological aspects can influence the behavior and personality of the people. It influences them to be more progressive to achieve their goal of life.